Mutations in XPR1 cause primary familial brain calcification associated with altered phosphate export - Legati, Andrea (Nat Genet, 2015)
Primary familial brain calcification (PFBC) is a neurological disease characterized by calcium phosphate deposits in the basal ganglia and other brain regions, thus far associated with SLC20A2, PDGFB, or PDGFRB mutations. We identified in multiple PFBC families mutations in XPR1, a gene encoding a retroviral receptor with phosphate export function. These mutations alter phosphate export, providing a direct evidence of an impact of XPR1 and phosphate homeostasis in PFBC.